Pengaruh suhu pada proses thawing terhadap kualitas spermatozoa sapi PO - ghopa Euhebius; Dirwan Muchlis; Dance Dance Fangindae (Faculty of Agriculture, Musamus University, 2019)
The potential of PO cattle in Merauke is quite high, this is the basis for the government to establish Merauke as one of the regions in eastern Indonesia as a center for beef cattle breeding. Efforts to increase population are carried out by utilizing reproductive technology in the form of artificial insemination (IB). IB failure can be caused by a number of factors including low quality of semen, unskilled inseminators and inaccurate detection of lust. The low quality factor of frozen semen can be caused by the post thawing process which affects the motility and viability. Therefore this study aims to determine the effect of different temperatures in the field on the quality of post thawing semen. The method used in the form of macroscopic test of semen quality includes Motility, viability and abnormality The results showed that the thawing process with a temperature of 38oC for 30 seconds was the best time and the percentage of spermatozoa motility and viability reached 65.2% ± 0.5 and 72.2% ± 0.4. The conclusion of this study is that the best temperature in the post thawing process for PO frozen semen is 38oC for 30 seconds, and this result is normal in accordance with Indonesian national standards for frozen semen.